An empirical analysis of the career expectations of women in science and technology courses - Preston, Alison (Centre for Workplace Culture Change RMIT, 2006)
Using data from a recent survey of first year university students, this study examine the career and occupational expectations of students enrolled in science and technology courses as a way of shedding further light on the labour market outcomes of women in these fields. It has been suggested that women's apparent lack of career success in science and technology stems from factors such as their lack of motivation and career commitment. Findings in this study show shared career goals and expectations between young male and female science technology students, but differences in expected family care plans. Young women typically see themselves balancing work and family responsibilities through engagement in part-time work, while young men typically envisage that they will work full-time and take on the main breadwinner role. The findings highlight the likelihood of an ongoing masculine culture within science and technology and call for efforts to ensure quality part-time work if the industry is to avert ongoing skill shortages and retain highly qualified women who hold similar career aspiration to men.